UJI DAYA HAMBAT EKSTRAK DAUN KEDONDONG (LANNEA GRANDIS ENGL) TERHADAP PERTUMBUHAN BAKTERI ERWINIA CAROTOVORA - Sudira, I Wayan; Merdana, I Made; Wibawa, I Putu Agus Hendra (Buletin Veteriner Udayana; Vol. 3 No. 1 Pebruari 2011)
Research with the title of the inhibition test kedondong leaf extract (Lannea grandisENGL)on the growth of bacteria Erwinia carotovora, causes soft rot of Aloe vera have beenconducted in vitro on media PPGA and testing of antibacterial activity of leaf extractkedondong on aloe vera leaf pieces. This study aims to determine the bactericidal activityof leaf extract and concentration kedondong minimal constraints on the growth ofbacteria Erwinea carotovora. Bacteria E. Carotovora isolated from the Aloe Vera plant softrot disease.Sections of leaves among the sick and the healthy cut to the size of ± 3 cm andcleaned with water and then soaked with 70% alcohol for 2 minutes inserted into laminar flow. Leaves clean kedondong have weighed as much as 100 grams chopped, then addedwith 1000 ml of methanol solvent. Immersion extract was filtered with filter paper watmanNo. 2.The filtrate obtained was evaporated by vacuum rotary evaporator to separate thesolvent (methanol) and the extract, made up to concentration. Bacteria isolated on mediapropagated PPGA tilted as stock for testing bacterial pathogens isolated colony of yellowwhitecolor with the aroma of sulfur-like smell of gas.Based on research results, it can beconcluded that the leaf extract could inhibit bacterial growth kedondongE carotovora withdoses at least 4% concentration in media PPGA and pieces of aloe vera leaves, whereas atconcentrations of 1, 2 and 3% have not been able to provide inhibition.
Keywords: Growth inhibition, Extract kedondong, Aloe vera